2021
DOI: 10.3389/fmed.2021.654573
|View full text |Cite
|
Sign up to set email alerts
|

Diversion Colitis and Probiotic Stimulation: Effects of Bowel Stimulation Prior to Ileostomy Closure

Abstract: Background: Diversion colitis is a non-specific inflammation of a defunctionalised segment of the colon after a temporary stoma has been performed. This inflammation is associated with a change in the colonic flora.Aim: To evaluate the efficacy and safety of preoperative stimulation of the efferent loop with probiotics prior to closure of the protective ileostomy in patients operated on colorectal carcinoma and its effect on diversion colitis. A prospective, randomised, double-blind, controlled study is carrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…The loss of diversity together with SCFA-producing bacteria is consistent with inflammatory states such as in IBD as confirmed by other studies (Ferrie et al, 2020). While the direction of cause and effect is not immediately clear, a recent RCT found that probiotic stimulation of the diverted bowel loops significantly improved clinical and histological signs of severe and moderate DC in 100% and 88% of patients, respectively (Rodríguez-Padilla et al, 2021). This points towards an active role of the microbiome in modulating immunity and function rather than simply being a biomarker of dysbiosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The loss of diversity together with SCFA-producing bacteria is consistent with inflammatory states such as in IBD as confirmed by other studies (Ferrie et al, 2020). While the direction of cause and effect is not immediately clear, a recent RCT found that probiotic stimulation of the diverted bowel loops significantly improved clinical and histological signs of severe and moderate DC in 100% and 88% of patients, respectively (Rodríguez-Padilla et al, 2021). This points towards an active role of the microbiome in modulating immunity and function rather than simply being a biomarker of dysbiosis.…”
Section: Resultsmentioning
confidence: 99%
“…Potentially harmful. Limited data but increases associated with malnutrition and coeliac's (Raineri et al, 2021;Rodríguez-Padilla et al, 2021).…”
Section: Decreasedmentioning
confidence: 99%
“…Researchers have attempted several approaches to mitigate these complications following ileostomy reversal, including the stimulation of the defunctioned bowel using saline or diluted ileostomy output [ 29 ] and preoperative administration of probiotics [ 30 , 31 ]. However, these interventions currently lack robust clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, the actual incidence rate of DC might be underestimated. According to studies ( 15 ), the most common symptoms in DC patients are serous, bloody, or mucous stools (40%), followed by abdominal pain and tenesmus (15%). In this study, the incidence rate of abdominal pain, mucus stool, and bloody stool were lower than other studies.…”
Section: Discussionmentioning
confidence: 99%